Kenyan teachers’ experiences of an online professional development program across rural, peri-urban, and urban settings - Wood, Eileen; Santhosh, Edwin; Gottardo, Alexandra; Battaglia, Noah; Chovu, Livison; Ghaa, Clifford; Wade, Anne; Vogel, Natasha (International Journal of Educational Technology and Learning, 2024)
The present study investigated Kenyan primary school teachers’ learning and experiences with an online blended teacher professional development (TPD) program targeting early literacy instruction across three contexts rural, peri-urban, and urban environments. In addition, examination of resources and the physical environment available to teachers in each of these contexts was compared for a subsample of the schools. Overall, following the TPD, teachers demonstrated gains in domain knowledge and confidence teaching literacy content and they perceived working with technology positively. These outcomes did not differ as a function of context. Examination of resources and physical environments of classrooms highlighted a significant lack of resources both in general and in particular with respect to enhancing literacy, with these shortfalls evident across all three contexts.